A história e a cultura festiva do brasileiro nas narrativas de Sílvio Romero (1883-1888) - Nascimento, José Uesele Oliveira (2017)
The present research aims to define how the discourses, written and published in the second half of the 19th century, and present in Sílvio Romero's work were in dialogue to define a "place" for the national popular culture, in a confluence of manifestations that went from the field to the city, through its historical, ethnographic and literary narratives, in the collection and transmission of songs (folk songs), folk tales, customs, traditions, profans and religious festivals, devotions, cults, prayers, tracing a picture of the social constitution of the wonderful and fascinating popular universe erected by the discursive sign of Brazilian people's miscegenation, searching, in these entangled nodes, to find the fossilized roots of the past imaginary, in ourselves and in others, immersed in the fringe of the various stories told and refold by the simple people, and materialized in time and in the blotter of some intellectuals. Then we use some of the author's works, such as: Popular Songs of Brazil (1883), Popular Tales of Brazil (1885), Studies on Popular Poetry in Brazil (1888), The History of Brazilian Literature (1808), which present themselves as documentary contributions for the understanding of an era and its sociocultural mentality, besides being also constituted is the first written records on the national oral history literature.